The Relationship Between Work Motivation and Employee Performance in Women with Dual Roles - Yasmin Rahman; Annisa Warastri (Publikasi Indonesia, 2024)
This research aims to determine the relationship between work motivation and the performance of female employees who play a dual role in Sleman Regency's local government agencies. This dual role phenomenon is challenging for women, as they must fulfil their obligations as housewives and workers, potentially affecting their motivation and performance. This study used a quantitative approach with a correlational method. The research subjects were married female employees aged between 20-57 years who work in government agencies in Sleman Regency. The sampling technique used was purposive sampling with specific criteria. Data were collected using a Likert scale measuring work motivation and employee performance. The data analysis using SPSS 25 showed a significant positive relationship between work motivation and the performance of female employees in dual roles (r = 0.480, p = 0.000). This finding indicates that the higher the work motivation, the higher the performance displayed by female employees, even though they also have responsibilities at home. This research contributes to understanding how work motivation can influence women's performance in the face of dual role demands and provides recommendations for policies that support women's well-being in the workplace